Prediction method of oil-water interface between injection and production wells in fault-controlled fractured-cavity reservoirs - WANG Yuanzheng; CAO Renyi; JIA Pin (Shenzhen Daxue xuebao. Ligong ban)
Fracture-controlled fracture-vuggy carbonate reservoirs are governed by extensive scale slip fracture modification within the craton and the longitudinal development of fracture-composite reservoir body (fracture-cavern body), which serves as both a channel for oil and gas transportation and reservoir space, exhibiting intricate spatial and configurational interdependencies. At present, there is no reasonable model to realize the precise classification and prediction of oil-water interface and water breakthrough rule during waterflood development, along with the formulation of subsequent development strategies and mitigative measures to address the existing predicament. In this study, based on the oil-water interface transport characteristics under a single cavern, a novel mathematical model of oil-water transport under multiple cavern connectivity in fault-controlled fracture-vuggy reservoirs is established by using the material balance equation. Furthermore, a real-time tracking and prediction approach for the dynamic oil-water interface between injection and extraction wells is devised based on the steady-state stepwise substitution method. In contrast to traditional numerical simulation approaches, this model is straightforward to formulate, remarkably efficient, and considers variations in oil-water density, as well as the intricate longitudinal arrangement of well-fracture-cavity systems. Consequently, it enables precise forecasting of water pattern of the production wells, the location of the oil-water interface in the cavities, and the distribution of residual oil and other development indexes. The results of the study show that multi-seam cavern development unit is affected by the production system and seam-cave reservoir parameters, and there will be three phases of well production (pure oil, oil-water co-production, and pure water period). Reasonable oil recovery and injection water rate can effectively maintain the formation pressure, balancing production efficiency and fracture stress sensitivity. As fracture conductivity increases, reservoir energy recovery accelerates, leading to a more rapid ascent of the oil-water interface. Furthermore, with the increase of cavern volume and fracture conductivity difference between injection and extraction wells, the oil-water co-production period will become longer. Finally, this paper compares the difference between the results of Eclipse numerical simulator and the calculation results of the model in this paper, and analyzes the influence of the physical parameters of the cavern body on the transport speed of the oil-water interface. In view of the current geological structure of fault-controlled fracture-vuggy reservoirs and the diversity of fracture-cavern body configuration relationships, it is an effective method to carry out real-time fitting of production dynamics of multiple wells with the results of the model prediction for the assessment and continual tracking of the oil-water interface. The proposed model provides a theoretical foundation and methodology for early warning of water breakthrough, optimization of injection and recovery parameters, and formulation of countermeasures for residual oil recovery in fault-controlled fracture-vuggy reservoirs.